Respuesta :

So,

[tex]2 \sqrt{9x} - 6 = 10 - 2 \sqrt{x} [/tex]

Simplify radicals first.
[tex]6 \sqrt{x} - 6 = 10 - 2 \sqrt{x} [/tex]

Try to combine the radicals.
[tex]8 \sqrt{x} - 6 = 10[/tex]

Isolate the radical.
[tex]8 \sqrt{x} = 16[/tex]

Power both sides.
[tex]64x = 256[/tex]

Divide both sides by 64.
[tex]x = 4[/tex]

Check
[tex]2 \sqrt{9(4)} - 6 = 10 - 2 \sqrt{4} [/tex]

Simplify radicals.
[tex]2 \sqrt{36} - 6 = 10 - 2 \sqrt{4} [/tex]
[tex]2(6) - 6 = 10 - 2(2)[/tex]

Perform multiplication.
[tex]12 - 6 = 10 - 4[/tex]

Perform subtraction.
[tex]6 = 6\ This\ checks.[/tex]

S = {4}
ACCESS MORE